Literal meaning - Récanati, François, 1952- (Cambridge University Press, 2004)
Do we need pragmatics to fix truth-conditions? What is 'literal meaning'? To what extent is semantic composition a creative process? How pervasive is context-sensitivity? François Recanati defends 'contextualism' and offers an informed survey of the spectrum of positions held by linguists and philosophers working at the semantics/pragmatics interface.